Acţiunea diferitor metode de întreţinere a solului utilizat sub livezi asupra proprietăţilor lui fizice şi chimice [Articol] - Grițcan, Sava; Nagacevschi, Tatiana (Tipografia "Reclama", 2013)
Contemporary requirements necessary to develop a national strategy based on a scientific ally based concept, oriented to efficient use, control of productivity and protection of soils. Method of soil maintenance in orchards influences soil fertility: humus content in sodded and mulched with substrate variants is higher in comparison with fallow land; congruent are characterized soil physical properties. Sodding, mulching space between rows should be alternated with fallow land and in strips along the line should be alternated mechanical, biological and chemical methods
Keywords: maintenance; black field; grassing; mulching; herbicides; structural units; nutritious regime